Mechanosensing is critical for axon growth in the developing brain - Koser, David E.; Thompson, Amelia J.; Foster, Sarah K.; Dwivedy, Asha; Pillai, Eva K.; Sheridan, Graham K.; Svoboda, Hanno; Viana, Matheus; Costa, Luciano da F.; Guck, Jochen; Holt, Christine E.; Franze, Kristian (Nature neuroscience, 2016)
Much of what is known about nervous system development is based on chemical signaling. In this study, Koser et al. demonstrate that developing neurons also respond to mechanical signals and that local tissue stiffness is a regulator of neuronal growth in vivo.
Gesehen am 20.05.2020